2008
DOI: 10.1038/nbt1366
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-conjugated antisense oligonucleotides for targeted inhibition of a transcriptional regulator in vivo

Abstract: Transcription factors are important targets for the treatment of a variety of malignancies but are extremely difficult to inhibit, as they are located in the cell's nucleus and act mainly by protein-DNA and protein-protein interactions. The transcriptional regulators Id1 and Id3 are attractive targets for cancer therapy as they are required for tumor invasiveness, metastasis and angiogenesis. We report here the development of an antitumor agent that downregulates Id1 effectively in tumor endothelial cells in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 44 publications
2
81
2
Order By: Relevance
“…42 The current findings are consistent with those from prior studies that have demonstrated that a loss of Id1 can lead to structural and functional vascular abnormalities in tumorbearing mice. 19,32,43 However, the present study could not distinguish whether the observed vascular abnormalities are a consequence or a cause of the more severe colitis. Nonetheless, our data suggest that the depletion of ID1 in the endothelium contributes to hypoxia, which can exacerbate inflammation.…”
Section: Discussioncontrasting
confidence: 42%
“…42 The current findings are consistent with those from prior studies that have demonstrated that a loss of Id1 can lead to structural and functional vascular abnormalities in tumorbearing mice. 19,32,43 However, the present study could not distinguish whether the observed vascular abnormalities are a consequence or a cause of the more severe colitis. Nonetheless, our data suggest that the depletion of ID1 in the endothelium contributes to hypoxia, which can exacerbate inflammation.…”
Section: Discussioncontrasting
confidence: 42%
“…These results indicate the importance of Id1 to the regulation of cell proliferation and suggest that the levels of Id1 are partly responsible for the difference in the effect of HGF on cell proliferation. Furthermore, recent reports showed the expression of Id1 to be related to the serum-independent proliferation of cancer cells (62), invasive behavior, and metastasis of tumors (29,31,33,35), suggesting that Id1 expression is involved in not only the regulation of cell proliferation in vitro but also carcinogenesis and malignant cell behavior in vivo. Therefore, our results showing the rapid down-regulation of Id1 induced by HGF and the signaling pathways responsible for the down-regulation are expected to provide a molecular basis for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Id1 is increased in proliferating cells and decreased by the induction of cell differentiation, and ectopic expression of Id1 represses the differentiation of some kinds of cells (26)(27)(28), suggesting that Id1 is a key regulator for the proliferation and differentiation of cells. Id1 is also considered a target in cancer therapy (29)(30)(31), because it is expressed in a wide variety of primary human tumors, such as endothelial, breast, prostate, and cervical cancers, and squamous cell carcinoma (32)(33)(34)(35)(36), and its expression is involved in malignant cell behavior (36). Although accumulating evidence indicates important biological effects of Id1, signaling pathways and signaling molecules responsible for the expression of Id1 are not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…However, molecular methods of preparing these materials are relatively inefficient, limit sequence diversity because of incompatible chemistries, require orthogonal protecting groups on nucleosides and amino acids (44), and can generate undesired side products (45). Thus, the synthesis and purification of heterofunctional molecules is a challenge.…”
mentioning
confidence: 99%